Epidemiology of Periprosthetic Fractures After Cementless Revision Total Hip Arthroplasty with Tapered, Fluted Stems at a Mid- to Long-Term Follow-Up - Bischel, Oliver E.; Jung, Matthias; Suda, Arnold J.; Seeger, Jörn B.; Böhm, Paul M. (Journal of Clinical Medicine, 2025)
Background: Although tapered and fluted stems are frequently used in revision total hip arthroplasty (RTHA), major complications following the implantation of these implants, like periprosthetic fractures, are less investigated. As epidemiological data do not exist yet, the incidence of PPF in a mid- to long-term follow-up is unknown and potential risk factors have not been detected. Methods: Propensity score matching (PSA) of two retrospectively investigated cohorts after femoral RTHA with either modular (n = 130) or monobloc prosthesis (n = 129) was executed. A total of 186 cases, including 93 of each device, were finally analyzed during a mean follow-up period of 9.1 (0.5-23.1) years. The time-dependent risk of PPF was calculated using a Kaplan-Meier analysis. Results: The cumulative risk for PPF of the whole cohort was 5.7% (95% CI: 1.7-9.8%) at 23.1 years, for the modular device, 13.0% (95% CI: 0-26.0%) after 13.7 years and the monobloc stem, 3.4% (95% CI: 0-7.1%) after 23.1 years, without a significant difference between the two designs (log-rank p = 0.1922). All eight fractures occurred in women and there was one collapse of the fracture after open reduction and internal fixation. The cumulative risk was 10.1% (95% CI: 3.1-17.1%) at 23.1 years compared to 0% after 21.4 years in men (log-rank p = 0.0117). Diabetes was significantly associated with the presence of PPF during follow-up (non-diabetic, 4.4% (95% CI: 0-8.2%) after 21.3 years vs. diabetic, 16.6% (96% CI: 0-34.5%) after 13.3 years; log-rank p = 0.0066). Longer reconstructions showed also a significantly higher fracture risk (equal or longer than median implant length vs. shorter; 10.5% (95% CI: 3.1-17.1%) after 21.4 years vs. 1.0% (95% CI: 0-3.1%) after 23.1 years; log-rank p = 0.0276) but did not correlate with a preoperative defect situation. Conclusions: The cumulative risk for PPF after femoral revision with tapered and fluted devices is a relevant failure reason in this mid- to long-term investigation. There was no difference between the monobloc stem or modular implant. Women and diabetics are at risk, and the choice of a longer implant than necessary is neither prophylactical for PPF nor useful in the case of the operative treatment of a PPF after femoral RTHA with these revision devices.